Inverse modeling of mass transferprocess in the RDC column by fuzzy approach - Maan, Normah; Talib, J.; Arshad, K. A.; Ahmad, T. (WSEAS Press, 2003)
Inverse modeling is natural in many real world application including industrial chemical engineering problems. This paper describes the process of determines optimal input and output of number of drops in various stage of rotating disc contactor column using fuzzy model. An algorithm of the fuzzy model is developed to simulate the above process. Inverse model to determine the optimal number of drops of RDC column using fuzzy approach.